The Effect of Health Education on Basic Life Support on Increasing The Knowledge And Skills of Female Students In Christian High Schools Schwarz Langowan - Kalangie, Wulan Jeynita; Killing, Maykel A.; Damping, Hendrik Herman (Jurnal Ilmiah Perawat Manado (Juiperdo), 2022)
Background: A life-threatening emergency condition where a person experiences cardiac arrest, respiratory arrest, or both, the causal factors include heart disease and traffic accidents so that this case can result in death. For this reason, increasing knowledge, especially for ordinary people, in providing first aidpre hospital necessary. Basic life support (BHD) is an emergency measure to clear the airway, assist breathing and maintain blood circulation without the use of assistive devices. In order to increase knowledge and skills for lay people, in this case female students, they are given health education about BHD. Puerpose:determine the effect of health education about basic life support on increasing the knowledge and skills of students at Schwarz Langowan Christian High School Method:This study used a one group pre test-post test design on 30 respondents to compare knowledge about BHD before and after health education was carried out. Data were collected through BHD knowledge questionnaires and BHD technique observation sheets. Data analysis used the Wilcoxon Signed Rank test with significance α < 0.05.Results: Knowledge results before being given treatment were (77%) in the sufficient category with an average value of 8.5333 and after being given treatment (90%) were in the good category with an average value of 15.2667. Skills before treatment (93%) were in the less skilled category with an average value of 1.8000 and after being given treatment (70%) were in the skilled category with an average value of 9.2333. Further analysis of both knowledge and skills of all respondents increased with the results of the analysis showing a significant influence of basic life support health education on knowledge and skills with a value of p = 0.000; α < 0.05. Conclusion:The conclusion is that health education about BHD has a significant effect on the level of knowledge and skills of students at Schwarz Langowan Christian High School. BHD's health education recommendations to improve knowledge and skills can be used as programs in schools to benefit all students. Keywords:Health Education, Basic Life Support, Knowledge, Skills